2020
DOI: 10.5935/1518-0557.20190074
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fresh IVF cycle characteristics on frozen embryo transfer (FET) outcomes

Abstract: Objective: To determine the effect of fresh IVF/ICSI cycles on FET cycle embryo and pregnancy outcomes.Methods: This retrospective cohort study included data from the medical records of 104 FET cycles performed from January 2014 to December 2016. Embryos were previously vitrified and then thawed for embryo transfer. Statistical significance was established at p<0.05. The main endpoints were FET cycle survival and pregnancy rates.Results: A total of 104 FET cycles were analyzed for survival; 94 showed good prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
(88 reference statements)
4
6
0
Order By: Relevance
“…Our results regarding the effect of previous fresh cycles on FET cycles are in agreement with the findings reported by Ashrafi et al (2011) and Bushaqer et al (2020), but in contrast with the reports from Doherty et al (2014) and Bdolah et al (2015). Our results showed that the clinical pregnancy rate in cases of FET with a history of successful early pregnancy was significantly higher than cases with the failed pregnancy history (61.30% vs. 43.53%), which means that the previous fresh cycle protocol may affect the pregnancy outcomes arisen from subsequent FET cycles.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results regarding the effect of previous fresh cycles on FET cycles are in agreement with the findings reported by Ashrafi et al (2011) and Bushaqer et al (2020), but in contrast with the reports from Doherty et al (2014) and Bdolah et al (2015). Our results showed that the clinical pregnancy rate in cases of FET with a history of successful early pregnancy was significantly higher than cases with the failed pregnancy history (61.30% vs. 43.53%), which means that the previous fresh cycle protocol may affect the pregnancy outcomes arisen from subsequent FET cycles.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that the clinical pregnancy rate in cases of FET with a history of successful early pregnancy was significantly higher than cases with the failed pregnancy history (61.30% vs. 43.53%), which means that the previous fresh cycle protocol may affect the pregnancy outcomes arisen from subsequent FET cycles. However, the previous fresh cycle outcomes did not affect the live birth rate, which confirms the results reported by El-Toukhy et al (2003) and Bushaqer et al (2020). Their results showed that embryo survival arisen from frozen cycle is not affected by the fresh cycles (Bushaqer et al 2020;El-Toukhy et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“… 8 As known, PCOS patients refer to high responder group, hence, elective freeze-all strategy is recommended worldwide to prevent OHSS, and to alleviate the harmful effects of supra-physiologic steroid hormones on the endometrium before embryo implantation. 9 Chen et al reported that FET increases live birth rates (LBRs) in their RCT of women with PCOS. 10 …”
Section: Introductionmentioning
confidence: 99%
“…IVF had become an important therapeutic technique for infertility of PCOS 8 . As known, PCOS patients refer to high responder group, hence, elective freeze-all strategy is recommended worldwide to prevent OHSS, and to alleviate the harmful effects of supra-physiologic steroid hormones on the endometrium before embryo implantation 9 . Chen et al reported that FET increases live birth rates (LBRs) in their RCT of women with PCOS 10 .…”
Section: Introductionmentioning
confidence: 99%